Peran pola asuh orang tua terhadap perundungan siber dimediasi kecenderungan depresi remaja - Lesmana, Teguh; Theresia, Allessandra; Rorong, Putri Daniela Ekaristia (Jurnal Psikologi Ulayat, 2025)
Previous studies have shown that parenting plays a significant role in adolescents' emotional and social development, which can influence their involvement in cyberbullying. This study examines the mediating role of depression tendencies in the relationship between parenting and cyberbullying behavior as a perpetrator. This study used a quantitative survey method with a cross-sectional approach on 165 adolescents who actively use social media, as well as mediation analysis using the JASP program. The results showed that authoritative parenting and neglectful parenting played a role in cyberbullying behavior through depression as a partial mediator. These findings emphasize the importance of authoritative parenting as a protective factor against cyberbullying, while neglectful parenting is a risk factor. The implications of this study underline the need for cyberbullying prevention interventions through education for parents about the importance of authoritative parenting, as well as school-based approaches to improve adolescents' emotional regulation and social skills.